Performance and carcass traits of feeder calves scored for muscling, frame size, and condition - Allen, Dell M.; Kemp, Kenneth E.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2011)
Calves with different USDA frame sizes had similar carcass composition and quality when slaughtered within the recommended weight range for their frame size. Large-framed calves had higher dressing percentages and gained faster than medium- or small-framed calves. Condition score appeared more useful than muscling score to characterize calves' performance and carcass traits. Calves thin at weaning had poorer performance, lower marbling scores, less fat, and higher retail product percentages than calves in medium or fat condition at weaning. Medium condition calves gained faster, had less fat, higher retail product percentages, and lower marbling scores than fat calves. Calves with large frame, thick muscle, and medium condition scores performed best in the feedlot and produced more desirable carcasses.
Keywords: Beef; Performance; Carcass Traits; Feeder calves; Muscling; Frame size; Condition